2017
DOI: 10.3390/nu9030241
|View full text |Cite
|
Sign up to set email alerts
|

Serum Parathyroid Hormone Responses to Vitamin D Supplementation in Overweight/Obese Adults: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Obesity is often associated with vitamin D deficiency and secondary hyperparathyroidism. Vitamin D supplementation typically leads to the reductions in serum parathyroid hormone (PTH) levels, as shown in normal weight individuals. Meanwhile, the dose of vitamin D supplementation for the suppression of PTH may differ in overweight and obese adults. We conducted a systematic review and meta-analysis of randomized controlled trials to determine the dose of vitamin D supplementation required to suppress PTH levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 63 publications
(139 reference statements)
4
29
1
2
Order By: Relevance
“…When comparing the vitamin D and placebo groups following the intervention period, a decrease was found in PTH in the vitamin D group. This is an expected observation since a reduction of parathyroid hormone has been associated with vitamin D supplementation [35]. Similarly, bilirubin levels were reduced in both groups with more pronounced reduction in the vitamin D group.…”
Section: Discussionsupporting
confidence: 62%
“…When comparing the vitamin D and placebo groups following the intervention period, a decrease was found in PTH in the vitamin D group. This is an expected observation since a reduction of parathyroid hormone has been associated with vitamin D supplementation [35]. Similarly, bilirubin levels were reduced in both groups with more pronounced reduction in the vitamin D group.…”
Section: Discussionsupporting
confidence: 62%
“…The importance of vitamin D and calcium in bone health is well-established and recommendations for the optimal intake of these nutrients is now widely accepted (7). Similar to previous reports in healthy individuals and in certain chronic diseases, the current study found a significant negative association between PTH and 25OHD in correlation analysis (38)(39)(40)(41)(42). The association was noted to be curvilinear with an inflection point at approximately 100 nmol/l of 25OHD visualized in loess curves.…”
Section: Interpretation and Comparison To Previous Literaturesupporting
confidence: 85%
“…Results from one investigation show that serum 25(OH) D needs to be higher than 31 ng/mL to suppress PTH in normal weight adult populations [55]. Lotito, et al found that, lower doses of vitamin D along with calcium can also significantly suppress PTH in the meta-analysis [56].…”
Section: Discussionmentioning
confidence: 99%